How can we consider multi‐core fibre standard? - Kazuhide Nakajima; Takashi Matsui (IET Optoelectronics)
Abstract The authors provide an example roadmap for realising the space division multiplexing (SDM)‐based ecosystem. The authors investigate whether the new standard for multi‐core fibre can be specified by considering a 125 μm standard cladding diameter and backward compatibility with the existing single‐core single‐mode fibre. The authors propose that well‐planned standardisation activities need to be initiated considering mandatory technologies for realising the terrestrial SDM ecosystem in the near future.